2009
DOI: 10.1002/cyto.a.20703
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed labeling of viable cells for high‐throughput analysis of glycine receptor function using flow cytometry

Abstract: Flow cytometry is an important drug discovery tool because it permits high-content multiparameter analysis of individual cells. A new method dramatically enhanced screening throughput by multiplexing many discrete fixed cell populations; however, this method is not suited to assays requiring functional cellular responses. HEK293 cells were transfected with unique mutant glycine receptors. Mutant receptor expression was confirmed by coexpression of yellow fluorescent protein (YFP). Commercially available cell-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…These dyes also label lymphocytes with fluorescence of low variance, typically with a fluorescence standard deviation of \25% of the mean fluorescence intensity (MFI) (15), allowing the delineation of several discretely labeled populations. While live cell multiplexing has been investigated previously, the paucity of compatible vital dyes with fluorescence of low variance has meant only a maximum of 8-12 spectrally distinct cell clusters has been achieved (30). We have demonstrated that with CFSE, CTV, and CPD that up to six intensities of each fluorescent dye can be used in combination to generate an array of up to 216 discernable cell clusters allowing the simultaneous measurement of killing of target cells pulsed with numerous peptides at different concentrations and the inclusion of many replicates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These dyes also label lymphocytes with fluorescence of low variance, typically with a fluorescence standard deviation of \25% of the mean fluorescence intensity (MFI) (15), allowing the delineation of several discretely labeled populations. While live cell multiplexing has been investigated previously, the paucity of compatible vital dyes with fluorescence of low variance has meant only a maximum of 8-12 spectrally distinct cell clusters has been achieved (30). We have demonstrated that with CFSE, CTV, and CPD that up to six intensities of each fluorescent dye can be used in combination to generate an array of up to 216 discernable cell clusters allowing the simultaneous measurement of killing of target cells pulsed with numerous peptides at different concentrations and the inclusion of many replicates.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this assay has great potential to be used as a tool to evaluate the functional capacity of CTLs, following vaccination. Finally, there is great potential for the application of these live-cell fluorescent arrays in other areas of biology that might benefit from simultaneous screening of multiple live-cell events (16,30).…”
Section: Discussionmentioning
confidence: 99%
“…Cells were imaged using an automated high-content screening system using YFP-I152L fluorescence as an indicator of Cl Ϫ influx rate (Kruger et al, 2005;Gilbert et al, 2009). Briefly, HEK293 cells were cotransfected with mutant or WT pRK5-hGlyR␣1 and pcDNA3.1-YFP-I152L and plated into a 384-well plate (ϳ2.5 ϫ 10 3 cells/well).…”
Section: Methodsmentioning
confidence: 99%
“…The staining of live cells, however, has been more problematic with the availability of compatible vital dyes, and only 8-12 viable cells clusters has been achieved previously 9 . The ability to generate >250 uniquely fluorescently labeled viable and functioning cells reported here, relies on the properties of CFSE-like vital dyes.…”
Section: Discussionmentioning
confidence: 99%